2019
DOI: 10.3390/en12163166
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Low-Power-Consumption Piezoelectric Energy Harvesting Circuit Based on Synchronized Switching Technology

Abstract: This paper presents a study of a piezoelectric energy harvesting circuit based on low-power-consumption synchronized switch technology. The proposed circuit includes a parallel synchronized switch harvesting on inductor interface circuit (P-SSHI) and a step-down DC-DC converter. The synchronized switch technology is applied to increase the conversion efficiency of the circuit. The DC-DC converter is used to accomplish the impedance matching for different loads. A low-power-consumption microcontroller and discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Synchronized Switch Harvesting architectures reuse the own charge of C peh to invert the polarity of V peh upon I peh zerocrossing. They employ either an inductor (SSHI) (Sanchez et al [4], Du et al [16], Ramadass and Chandrakasan [17], Wu et al [18], Chamanian et al [19,20]) or a set of capacitors (SSHC) ( Chen et al [2], Du and Seshia [3], Chen et al [21], Hong et al [22]) to store the charge of C peh temporarily before sending it back once the electrodes of the PT have been swapped. Architectures combining both an inductor and a capacitor have also been reported in Çiftci et al [23] and Çiftci et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…Synchronized Switch Harvesting architectures reuse the own charge of C peh to invert the polarity of V peh upon I peh zerocrossing. They employ either an inductor (SSHI) (Sanchez et al [4], Du et al [16], Ramadass and Chandrakasan [17], Wu et al [18], Chamanian et al [19,20]) or a set of capacitors (SSHC) ( Chen et al [2], Du and Seshia [3], Chen et al [21], Hong et al [22]) to store the charge of C peh temporarily before sending it back once the electrodes of the PT have been swapped. Architectures combining both an inductor and a capacitor have also been reported in Çiftci et al [23] and Çiftci et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure exerted on the model causes a deflection, which leads to a linear electromagnetic interaction of the mechanical and electrical parts. Therefore, some parts of the material become positively charged, while others consist of negative electrodes, which cause the accumulation of an electric charge on the piezoelectric section [1]. Therefore, the greater the pressure applied, the greater the voltage and electric current generated by this piezoelectric material [3,7].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was discovered by the Curie brothers in 1880, by observing the semiconductor crystals that generated electricity due to the presence of external mechanical stress. The linear electromagnetic interaction of mechanical and electrical parts in the piezoelectric crystal material forms the positive and negative parts of the electrodes, which causes an accumulation of electric charges [1]. Furthermore, the deflection (direct piezoelectric) and the vibrations were produced by the electricity which comes from the pressure, pull, or vibration applied to the piezoelectric material [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another much explored technique to boost the performance is the interfacing of the piezoelectric devices with the power processing circuits. Several researchers have reported that the power from the piezoelectric elements can be enhanced up to 900% using power processing circuits such as synchronized switch harvesting 36‐38 . However, the polarization of the piezoelectric material has attracted the attention from researcher in the recent years, as a probable way to tailor and/or enhance the performance of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that the power from the piezoelectric elements can be enhanced up to 900% using power processing circuits such as synchronized switch harvesting. [36][37][38] However, the polarization of the piezoelectric material has attracted the attention from researcher in the recent years, as a probable way to tailor and/or enhance the performance of these materials. Yang et al 39 employed the combination of domain engineering and defect engineering by strategically controlling the poling process.…”
mentioning
confidence: 99%